2020
DOI: 10.1016/j.trf.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A simulation sickness study on a driving simulator equipped with a vibration platform

Abstract: Simulator sickness is a well-known side effect of driving simulation which may reduce the passenger well-being and performance due to its various symptoms, from pallor to vomiting. Numerous reducing countermeasures have been previously tested; however, they often have undesirable side effects. The present study investigated the possible effect of seat vibrations on simulator sickness. Three configurations were tested: no vibrations, realistic ones and some that might affect the proprioception. Twenty-nine part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In their experiment (simulated bicycle ride), the addition of vibration to the seat did not reduce the symptoms of SS. However, their results were challenged by recent published studies (Lucas et al 2020;Sawada et al 2020), which found instead that adding vibration to a driving simulator can reduce the level of SS in the users. The methods used by Sawada et al (2020) andD'amour et al (2019) for delivering the vibration were similar to the one used in our study (vibration device under the chair), while Lucas et al (2020) used a vibrating platform.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In their experiment (simulated bicycle ride), the addition of vibration to the seat did not reduce the symptoms of SS. However, their results were challenged by recent published studies (Lucas et al 2020;Sawada et al 2020), which found instead that adding vibration to a driving simulator can reduce the level of SS in the users. The methods used by Sawada et al (2020) andD'amour et al (2019) for delivering the vibration were similar to the one used in our study (vibration device under the chair), while Lucas et al (2020) used a vibrating platform.…”
Section: Discussionmentioning
confidence: 93%
“…The type of vibratory stimulation used in Weech et al (2018) might represent a more intense type of stimulation and have a greater effect than using a vibration chair. On the other hand, both the recent studies of Sawada et al (2020) and Lucas et al (2020) found that vibration reduced SS when a vibration chair or platform was used.…”
Section: Discussionmentioning
confidence: 93%
“…Although previous authors have reported that simulator sickness has deleterious effects on drivers’ performances [ 44 ], this was not the case in the present study. This may have been due to the presence of factors minimizing simulator sickness, such as a full car cabin and the motion of the car [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, simulator sickness is another aspect which has been widely studied in the field of virtual reality. Although this problem can be minimized by adapting factors such as the type of cabin [ 27 ] or the dynamics of the simulations [ 28 ], it is still an almost ubiquitous problem in the field of simulation, which can be increased by the occurrence of stress [ 29 ] or a strong feeling of presence [ 30 ]. The possibility of measuring this process should help to understand its influence and its interactions with all the parameters of interest, since it can influence drivers’ performances [ 31 ] and their physiological state in terms of parameters such as the heart rate [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite more than 40 years of research, it remains a core research topic. Lucas et al compared three vibration patterns (no vibration, realistic vibrations and vibrations affecting proprioception (between 60 Hz and 100 Hz)) and studied their influence on the level of simulator sickness (Lucas, Colombet, Paillot, & Kemeny, 2019). Results showed that realistic road vibrations lowered sickness levels compared to no vibration and vibrations affecting proprioception.…”
Section: Contributionsmentioning
confidence: 99%